2018
DOI: 10.1007/s00384-018-3143-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical teaching does not increase the risk of intraoperative adverse events

Abstract: Within a standardized teaching environment, colonic resections were safely performed regardless of the surgical setting in the present cohort. Teaching does not increase intraoperative adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…First, advanced expertise in robotic surgery allowed for safe surgery despite unfavorable and challenging conditions with complicated disease. Second, standardized approach and teaching conditions lead to better outcomes, as repeatedly shown previously [27][28][29]. Finally and most importantly, high compliance to the institutional ERP, yielding over 70% even in patients with complicated disease, may have significantly contributed to these encouraging results.…”
Section: Discussionmentioning
confidence: 71%
“…First, advanced expertise in robotic surgery allowed for safe surgery despite unfavorable and challenging conditions with complicated disease. Second, standardized approach and teaching conditions lead to better outcomes, as repeatedly shown previously [27][28][29]. Finally and most importantly, high compliance to the institutional ERP, yielding over 70% even in patients with complicated disease, may have significantly contributed to these encouraging results.…”
Section: Discussionmentioning
confidence: 71%
“…24,25 In studies involving colorectal resections, trainees performing surgery with the consultant mentors assisting have been shown to yield non-inferior outcomes when compared to consultants performing the surgery themselves. [26][27][28][29] A survey of surgeon mentors also found that the ASU allowed more time for education and was beneficial for surgical training of juniors. 30 Several other studies also found that increased consultant presence increased registrar case load and satisfaction.…”
Section: Egs Should Be Consultant Ledmentioning
confidence: 99%
“…The involvement of consultant surgeons in emergency surgeries has resulted in decreased complication rates . In studies involving colorectal resections, trainees performing surgery with the consultant mentors assisting have been shown to yield non‐inferior outcomes when compared to consultants performing the surgery themselves …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 99%
“…With regard to laparoscopic colorectal surgery, it has been shown that residents during their final years very well can achieve results that do not affect patient safety and short-term outcome adversely [58]. And some authors did not find any difference in intraoperative adverse effects during colonic procedures when comparing consultants with trainees [59].…”
Section: Literature Regarding Training In Gep-netmentioning
confidence: 99%